Al-idrāk al-hissī ‘inda ṭullāb aṣ-ṣaff ats-tsānī ‘asyar lilughah al-‘Arabiyyah kamādah al-lughah al-ajnabiyyah fī madrasah ar-Raihān ats-tsānawiyyah bi Bandār al-Mabunj. - Muslim, Ahmad Bukhari; Harisca, Rodhy; Tafida, Adam Alhaji; Safitri, Nur (Journal of Applied Transintegration Paradigm, 2022)
The aim of this research is to carry out the process of researching the sensory perception among students of the Arabic language as a foreign language subject in the high school of Al-Rayhan Secondary School, Bandar Lampung. In writing this article, the researchers use the quantitative approach, and empirical research. The experimental research searches for the relationships between the correct variables (factors) to obtain a generalization. This research has two groups: the first is the experimental group, which is the group that is exposed to the experimental or independent variable, to know the effect of this variable on it. The second control group is the group that is not exposed to the experimental variable and remains under normal conditions. One of the results of this research is the emotional field of the 12th grade students of Arabic language as a foreign language subject in the high school of Al-Rayhan Secondary School, Bandar Lampung good. The intentional field for the 12th grade students of Arabic as a foreign language subject in the high school of Al-Rayhan Secondary School Bandar Lampung is good.